COVID-19 y biomasa en Perú: Entre necesidad y riesgo - León-Jiménez, Franco E.; Díaz-Vásquez, Maribel A.; Díaz-Manchay, Rosa J.; Malca-Díaz, Jimmy F.; Failoc-Rojas, Virgilio E. (Revista del Cuerpo Médico Hospital Nacional Almanzor Aguinaga Asenjo, 2021)
Carta al Editor (sin resumen)